CONCEPTS AND TYPES OF ADMINISTRATIVE SERVICES IN THE FIELD OF ENTREPRENEURIAL ACTIVITY (Bulletin of criminological association of Ukraine, 2023)
The article determines that administrative services in the field of entrepreneurial activity are aimed at providing socially significant benefits necessary for successful business in Ukraine, as well as preventing the transition of entrepreneurs to the "shadow" sector of the economy. By building a system of providing administrative services to the population, the state thereby ensures transparency, accountability, and effective control over the entire array of complex and multi-stage management processes, making it impossible for corrupt practices and organized crime to penetrate them.
Keywords: administrative services; entrepreneurial activity; concepts; types; digitization; administrative service provision centers